Tindak Bahasa Guru dalam Interaksi Belajar-Mengajar Bahasa Indonesia di Sekolah Dasar - Alif Mudiono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study was intended to explore teachers’ speech acts in the teaching-learning process of Bahasa Indonesia in the fourth grade of elementary schools. A descriptive-qualitative design was employed and data were collected from fourth-grade teachers of Bahasa Indonesia in elementary schools in Blitar through observation, interview, and field notes. Data analysis was carried out while and after collecting the data. The results indicate that the teachers used a variety of speech acts proportionally and effectively in accordance with developmental theories by Austin, Searle, Flanders, Sinclair and Coulthard, and Burton. The teachers’ speech acts reflect the success of communicative interaction in the teaching-learning process.